Clinical Characteristics and Treatment Options of Peripheral Spondyloarthritis - ZENG Lulu; JI Xiaojian; HU Lidong; HU Jiawen; ZHANG Yinan; ZHANG Jiaxin; LIU Xingkang; YANG Shiwei; HUANG Feng (Xiehe Yixue Zazhi)
ObjectiveTo compare the differences in clinical features and treatment choices between peripheral spondyloarthritis(pSpA) and axial spondyloarthritis(axSpA), and better understand the clinical characteristics and medication needs of pSpA.MethodsOur study is a retrospective cohort study. The patients who first visited the First Medical Center of Chinese PLA General Hospital between January 2016 and December 2022 and were diagnosed with axSpA or pSpA according to the classification criteria established by the Assessment of SpondyloArthritis International Society were selected as the study subjects. Demographic data, clinical characteristics, laboratory tests, and treatment information of these patients were obtained through the electronic medical records management system and the intelligent management system for spondyloarthritis. The research compared the distribution of swollen and tender joints between pSpA and axSpA patients, as well as that between pSpA1(excluding patients with psoriatic arthritis) and axSpA patients. Additionally, we analyzed differences in clinical features and treatment options among these groups.ResultsA total of 1639 patients were included in the study, of which 184 had pSpA(including 97 with psoriatic arthritis), and 1455 had axSpA. Compared to axSpA patients, pSpA patients had fewer male patients(62.5% vs. 79.7%, P < 0.001), later onset age(33.8 years vs. 22.0 years, P < 0.001), shorter diagnostic delays(6.0 months vs. 14.2 months, P=0.004), more associated peripheral arthritis(71.7% vs. 9.3%, P < 0.001) and dactylitis(6.5% vs. 0.3%, P < 0.001), more cases of psoriasis(52.7% vs. 1.1%, P < 0.001) and a more common family history of psoriasis(11.4% vs. 3.4%, P < 0.001). pSpA patients had higher levels of inflammatory markers but a lower positive rate of human leukocyte antigen(HLA)-B27(43.5% vs. 87.4%, P < 0.001). A positive HLA-B27 was associated with an earlier onset age, fewer cases of psoriasis, and a family history of ankylosing spondylitis. pSpA patients had a higher proportion of using conventional synthetic disease-modifying antirheumatic drugs(csDMARDs), biologic disease-modifying antirheumatic drugs(bDMARDs), and oral glucocorticoids, and they also more frequently used a combination of bDMARDs and csDMARDs(19.0% vs. 12.2%, P=0.009) or multiple csDMARDs(65.8% vs. 12.5%, P < 0.001). Compared to axSpA patients, pSpA1 patients(excluding psoriatic arthritis) did not show significant differences in the prevalence of psoriasis, uveitis, family history of psoriasis, or the use of bDMARDs, but the subgroup analysis of other variables was consistent with the results of pSpA patients.ConclusionspSpA patients tend to have a later onset of disease, a lower proportion of male and HLA-B27 positivity, more associated peripheral arthritis, dactylitis, psoriasis, and a more common family history of psoriasis. The disease burden in terms of treatment for pSpA is not lower than that for axSpA. Due to the presence of more peripheral symptoms, psoriasis, and higher levels of inflammation, they also require more medication.